PENGARUH PENGGUNAAN ALAT PERAGA MODEL ATOM 3 DIMENSI BERBASIS PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM DI KELAS X MAN 2 FILIAL PONTIANAK - Sukma Dewi; Mawardi Mawardi; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2017)
BSTRACTThis research had the purpose to find out the differences and influences between the students’ learning outcomes which were taught by using props 3-dimensional atomic model-based learning Think Pair Share (TPS) to the learning outcomes of students in the structure of atoms lecture in class X MAN 2 Filial Pontianak. The sampling technique using sampling saturated with class X IIS as experimental class and class X MIA as the control class. Data collecting techniques using measurement techniques, observation and interviews, data collecting tools are achievement test, and observation sheet. The result showed that the average value posttest experimental class (73.33) was higher than the average value posttest control group (44.22). Statistical analysis Mann Whitney U-test (α = 0.05) p value obtained is 0.00 means that there are significant differences in learning outcomes between the experimental and control classes. Calculations using the effect size indicates the value of ES = 1.47 means the use of props threedimensional atomic model-based learning Think Pair Share (TPS) had much effect on student learning outcomes in the amount of 42.92%.Keywords: Props, Learning Outcomes, Atomic Structure, Think Pair Share